Effects of Music Listening on Cortisol Levels and Propofol Consumption during Spinal Anesthesia - Koelsch, Stefan; Fuermetz, Julian; Sack, Ulrich; Bauer, Katrin; Hohenadel, Maximilian; Wiegel, Martin; Kaisers, Udo; Heinke, Wolfgang (Frontiers in Psychology, 2011)
Background: This study explores effects of instrumental music on the hormonal system (as indicated by serum cortisol and adrenocorticotropic hormone), the immune system (as indicated by immunoglobulin A) and sedative drug requirements during surgery (elective total hip joint replacement under spinal anaesthesia with light sedation). This is the first study investigating this issue with a double-blind design using instrumental music. Methodology / Principal Findings: Patients (n = 40) were randomly assigned either to a music-group (listening to instrumental music), or to a control-group (listening to a non-musical placebo stimulus). Both groups listened to the auditory stimulus about 2 hours before, and during the entire intra-operative period (during the intra-operative light sedation, subjects were able to respond lethargically to verbal commands). Results indicate that, during surgery, patients of the music-group had a lower propofol consumption, and lower cortisol levels, compared to the control-group. Conclusions / Significance: Our data show that listening to music during surgery under regional anaesthesia has effects on cortisol levels (reflecting stress-reducing effects) and reduces sedative requirements to reach light sedation.